Efficacy of Tranexamic Acid on Perioperative Blood Loss in Hip Arthroplasty: A Comparative Study - Shantanu Vijay; Subham Verma; Bharat Soni; Tarun Desai; Prashant Alwani; Jeevan Kishor Appala; Chirag Valentine Thakkar (Journal of Orthopedic and Spine Trauma, 2025)
Background: Using tranexamic acid (TXA) as a measure to ensure hemostasis during surgeries involving the hip region is a topic that is still debated, with scarce literature. The aim of this study was to assess the effectiveness of TXA administration in improving outcomes of hip arthroplasty. Methods: This is a randomized comparative prospective study. It was conducted in the Department of Orthopedics, GMERS Medical College and Hospital, Vadodara, India, from January 2023 to December 2023 on 60 patients undergoing hip arthroplasty. Results: The postoperative mean hemoglobin (Hb) value after 24 hours in the test group was 10.9 ± 1.6 g/dl while it was 10.1 ± 1.4 in the control group, which was statistically significant. The mean duration of surgery in the test group was 102.7 ± 28.2 minutes versus 125.2 ± 36.5 minutes in control with a P-value of 0.01, indicating less surgical duration in the test group. Conclusion: TXA is an effective agent to reduce intraoperative blood loss, reduce surgical time, and improve post-operative Hb levels.